Reseña/Review (Marxen, Eva ‘Deinstitutionalizing Art of the No-madic Museum. Practicing and Theorizing Critical Art Therapy with Adolescents’, New York, Routledge, ISBN: 978-1-351-11666-4 (ebk), 238 págs. 2020) - González Gutiérrez, Luis Felipe (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2021)
Reseña/Review (Marxen, Eva ‘Deinstitutionalizing Art of the Nomadic Museum. Practicing and Theorizing Critical Art Therapy with Adolescents’, New York, Routledge, ISBN: 978-1-351-11666-4 (ebk), 238 págs. 2020)